Estimating the Prevalence of and Clarifying Factors Associated With Multiple Tobacco Product Use in Japan: A Cross-sectional Study in 2022 - Takafumi Yamamoto; Hazem Abbas; Upul Cooray; Tetsuji Yokoyama; Takahiro Tabuchi (Journal of Epidemiology)
Background: Multiple tobacco product (MTP) use is a public health concern due to their combined adverse health effects. MTP use may have increased since heated tobacco products (HTPs) became more prevalent in Japan. This study aimed to (1) estimate the recent prevalence of MTP use and clarify the associated factors compared to (2) non-smokers and (3) single-product users. Methods: We used data from an internet survey conducted in February 2022. The prevalence of MTP use in Japan was estimated using inverse probability-weighted scores from this survey and a nationwide survey by the Japanese government. Tobacco products include six types: cigarettes, HTPs, e-cigarettes, cigars, pipe/water pipes, and smokeless tobacco products. MTP use was defined using the outcome variable (no use, single-product use, and MTP use) based on these six types of use. Using multivariate logistic regression, we calculated the adjusted odds ratios and 95% confidence intervals (CI) to clarify factors associated with MTP use compared to non-smokers, adjusting demographic variables, psychological distress, self-rated health, and alcohol use. Using multivariate Poisson regression, we calculated the adjusted prevalence ratios (aPRs) and 95% CIs to clarify factors associated with MTP use among smokers, adjusting for these covariates and smoking-related factors like workplace and home smoking rules. Results: We analyzed 30,141 participants whose mean age was 47.8 years (standard deviation, 17.9), and 14,722 participants were male (48.8%). The estimated prevalence of MTP use was 6.8%. The most common combination of MTP use was cigarettes and HTPs. Compared to non-smokers, being younger, male, alcohol drinkers, and having low education, poor psychological distress, and poor self-rated health were factors associated with MTP use. Among smokers, workplace smoking rules, such as a partial smoking ban and no smoking ban, were not associated with MTP use compared to the indoor smoking ban. However, having no home smoking ban was positively associated with MTP use compared with a ban on both cigarettes and HTPs at home (both cigarettes and HTPs allowed aPR 1.36; 95% CI, 1.15–1.61, HTPs only allowed aPR 1.73; 95% CI, 1.43–2.10). Conclusion: MTP users may account for a high percentage of Japanese smokers.